Paradoxes and hydrological inferences for the desert valleys extending between Haditha and Al-Ramadi using remote sensing data and geographic information systems. - Thekryat M. Mehimid; Ahmed Flaieh Fayadh (مجلة جامعة الأنبار للعلوم الإنسانية, 2023)
The hydrological characteristics of the valleys are considered part of its general system, as the research aims to shed light on these characteristics of the seven studied basins, by using the Snyder model to estimate the volume of runoff for those basins, and the highest amount of flow was reached at the Hauran Valley of (255.2) m3 / second followed by Al-Suhailia Valley, then Al-Mohammadi, with quantities amounting to (144.7, 120.8) m3 / sec, respectively, while the highest volume of tuberculosis in Wadi Hauran was (3.07) million m3, (1.5) million m3 in Suhailia Valley, and (1.4) million m3 in Zagdan Valley. These values ​​make them record the highest flooding incidents between valleys, which raises the risk ratios in them. As for the hydrograph curves, which is a creation based on morphometric characteristics and rain characteristics as well as surface characteristics of heights and slopes, and using the (WMS 10) program, the results showed that the time period is shorter in Wadi Zagdan in terms of the arrival of the flood wave to its peak, unlike Wadi Hauran, which is longer in time. Likewise, in Wadi Falij, the wave exceeds its absorptive capacity, as it takes a longer time compared to the size of the valley.